Pemuda dan Sagu: Perubahan Konsumsi Pangan Pokok di Kabupaten Halmahera Barat, Maluku Utara - Ahmad Syariful Jamili (Universitas Islam Madura, 2022)
Food diversification based on local food is one of the alternative efforts in anticipating food crises. Basically, the food consumption patterns of the population will generally be different and change over time, where youth have a strategic role in the future. Therefore, this study aims to record the current preference of a potential substitute for rice. The research was conducted in the area of the Banau College of Agriculture and Entrepreneurship, West Halmahera Regency, North Maluku. The results of the study indicate that there has been a change in the pattern of youth staple food consumption from local foods such as sago to rice. Based on consumption patterns, only some youths make sago a staple food. Rice is still the main preference of youth as staple food in everyday life. While sago is the second priority as a staple food in the menu of youth consumption patterns. There are several factors that cause changes in consumption patterns, including: 1) development policies and food policies on one food commodity, namely rice; 2) Conversion of sago forests into paddy fields; 3) public perception of sago; and 4) the culture of eating rice brought by transmigrants. Therefore, systematic efforts are needed from both the government, the private sector and the community to achieve food security. The local government is expected to be able to promote food diversification programs. The private sector can develop local food (sago) into derivative products that can be accepted by the wider community, such as noodles, bread, flour, cakes, etc. From the community side, efforts to diversify can be started from the family by diversifying daily staple foods. Society as the smallest unit in a country has an important role in the success of food diversification.